2020
DOI: 10.1556/650.2020.31625
|View full text |Cite
|
Sign up to set email alerts
|

A társas támogatás és az egészséges életmód összefüggései

Abstract: Absztrakt: Bevezetés: A cardiovascularis megbetegedések vezető haláloki tényezőként évente 4 millió halált okoznak Európában. Az életmód mellett 25–40%-ra becsülik a pszichoszociális tényezők szerepét a betegség létrejöttében. A felnőttkori szociális izoláció a krónikus stressz forrása, és másfélszeres rizikót jelent a betegség kialakulására. A társas támogatás alacsony szintje és a társas iz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(48 reference statements)
2
2
2
Order By: Relevance
“…As to different dimensions of mental health, from the reviewed literature it was Abiola and Ocsovszky who assessed correlations of depression and stress. While Abiola found that social support was not protective against depression, Ocsovszky's results demonstrated similarly to our results that stronger social support resulted in a lower prevalence of stress and depression (Abiola et al, 2013;Ocsovszky et al, 2020). A positive correlation between sense of coherence and social support was emphasized also by Getnet and Alem, though they evaluated a completely different focus group (Getnet & Alem, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…As to different dimensions of mental health, from the reviewed literature it was Abiola and Ocsovszky who assessed correlations of depression and stress. While Abiola found that social support was not protective against depression, Ocsovszky's results demonstrated similarly to our results that stronger social support resulted in a lower prevalence of stress and depression (Abiola et al, 2013;Ocsovszky et al, 2020). A positive correlation between sense of coherence and social support was emphasized also by Getnet and Alem, though they evaluated a completely different focus group (Getnet & Alem, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…When analyzing the correlations, reduction of social support in parallel with age was not confirmed in our sample against other pieces of literature (Abiola et al, 2013;Kocalevent et al, 2018;Ocsovszky et al, 2020). Furthermore, the family from social demographic factors did not prove to be significant among our participants (Ocsovszky et al, 2020). Regarding gender, again no significant correlation was found with social support similarly to Kocalevent's results and against Abiola's findings (Abiola et al, 2013;Kocalevent et al, 2018).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations